Sustaining the Innovation Culture in SMEs: The Importance of Organisational Culture, Organisational Learning and Market Orientation - Halim, Hasliza Abdul; Ahmad, Noor Hazlina; Ramayah, T. (MAG Scholar, 2019)
Previous research on innovation culture among SMEs has received little attention particularly in developing countries. Thus, this paper aims to investigate the influence of organisational culture, organisational learning and market orientation on innovation culture. A total of 183 usable responses were received from SMEs in Malaysia. Findings from the analysis suggest that all dimensions of organisational culture influence innovation culture while organisational learning in terms of information acquisition, behavioural and cognitive also influences innovation culture. Finally, in terms of market orientation, only competitor orientation influences innovation culture. This study contributes to SMEs by providing information on the elements that could nurture innovation culture in their organisations